The Other Women's Lib Gender and Body in Japanese Women's Fiction - Bullock, Julia C. (University of Hawai'i Press, 2010)
The Other Women's Lib provides the first systematic analysis of Japanese literary feminist discourse of the 1960s - a full decade before the "women's lib" movement emerged in Japan. It highlights the work of three well-known female writers of avant-garde fiction from this generation: Kono Taeko, Takahashi Takako, and Kurahashi Yumiko. Focusing on four tropes persistently employed by these writers to protest oppressive gender stereotypes - the disciplinary masculine gaze, feminist misogyny, "odd bodies," and female homoeroticism - Julia Bullock brings to the fore their previously unrecognized theoretical contributions to second-wave radical feminist discourse.The Other Women's Lib affords a cogent and incisive analysis of these texts as feminist philosophy in fictional form. It will be accessible to undergraduate audiences and deeply stimulating to scholars and others interested in gender and culture in postwar Japan, Japanese women writers, or Japanese feminism.